2020
DOI: 10.1101/2020.07.04.187906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astroglial Calcium Signaling Encodes Sleep Need inDrosophila

Abstract: SUMMARYSleep is under homeostatic control, whereby increasing wakefulness generates sleep need and triggers sleep drive. However, the molecular and cellular pathways by which sleep need is encoded are poorly understood. In addition, the mechanisms underlying both how and when sleep need is transformed to sleep drive are unknown. Here, using ex vivo and in vivo imaging, we show in Drosophila that as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…This finding aligns with studies showing heightened stimulus-evoked Ca 2+ activity in astrocytes during wakefulness, which diminishes during sleep (Bojarskaite et al, 2020;Ingiosi et al, 2020). In flies, Ca 2+ activity in astrocytes is correlated with the duration of wakefulness, suggesting that astrocytic Ca 2+ is a key factor in the homeostatic regulation of sleep (Blum et al, 2021). Our findings provide a mechanistic explanation for differential Ca 2+ levels observed between wake and sleep states, with circadian regulation of ITPR2 by HERP being a key factor in this process.…”
Section: Discussionsupporting
confidence: 90%
“…This finding aligns with studies showing heightened stimulus-evoked Ca 2+ activity in astrocytes during wakefulness, which diminishes during sleep (Bojarskaite et al, 2020;Ingiosi et al, 2020). In flies, Ca 2+ activity in astrocytes is correlated with the duration of wakefulness, suggesting that astrocytic Ca 2+ is a key factor in the homeostatic regulation of sleep (Blum et al, 2021). Our findings provide a mechanistic explanation for differential Ca 2+ levels observed between wake and sleep states, with circadian regulation of ITPR2 by HERP being a key factor in this process.…”
Section: Discussionsupporting
confidence: 90%
“…Astrocytic tumor necrosis factor-alpha (TNF-α), a pro-inflammatory cytokine, is an important sleep regulator. Several studies have shown that astrocyte-derived cytokines, including TNF-α and interleukin (IL)-1, support sleep and immunity (Krueger et al, 2011;Olivadoti et al, 2011;Blum et al, 2021), even though the function of TNF-α in sleep remains debatable (Szentirmai and Kapás, 2019). IL-6 can enhance adenosine A(1) receptor mRNA expression and signaling in astrocytes (Biber et al, 2001), and as mentioned above, adenosine is an established inhibitory neuromodulator that supports sleep homeostasis.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Additionally, after SD, less astrocyte synchronization occurred at both the network and single-cell levels during nonrapid eye movement sleep (Ingiosi et al, 2020). Another study on a Drosophila model indicated that specific astrocytic L-type Ca 2+ channel-dependent Ca 2+ signals increase to enhance sleep drive so that sleep demand can be met; moreover, increased levels of TyrRll (a monoaminergic receptor) in a Ca 2+ -dependent manner following SD can evoke further elevation of astrocytic Ca 2+ levels and promote a positive feedback loop that contributes to sleep homeostasis (Blum et al, 2021).…”
Section: Ca 2+mentioning
confidence: 99%